An experiment to determine the microstructures and mechanical properties of titanium fabricated by selective laser melting - Ng, Kevin Kian Wei (2016)
The objective of this project is to examine and analyse the microstructures and mechanical properties of Ti-6Al-4V titanium fabricated by selective laser melting (SLM). As technology advances, many industries began to develop their own machines to manufacture products. Additive manufacturing (AM) has provided geometric flexibility, time reduction and better efficiency in terms of material usage. These are key factors in order for the aviation industry to develop rapidly. Quality of the products are also greatly affected by printing process parameters. In the report, titanium alloy Ti-6Al-4V was fabricated through Selective Laser Melting (SLM) with two different laser energy density as parameter. The relative density, surface roughness, microstructure and mechanical properties were examined to find out if Ti-6Al-4V samples fabricated by SLM was affected by laser energy density. It was observed that the microstructure of titanium fabricated through SLM was of acicular martensites α’. After conducting different tests on the titanium samples, it was found that relative density, micro-hardness and strength increases with higher laser energy density however ductility decreases due to larger martensitic α’ phase at higher laser energy density.